2016
DOI: 10.1557/mrc.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet optoelectronic devices based on AIGaN alloys grown by molecular beam epitaxy

Abstract: This paper reviews progress in ultraviolet (UV) optoelectronic devices based on AlGaN films and their quantum wells (QWs), grown by plasmaassisted molecular beam epitaxy. A growth mode, leading to band-structure potential fluctuations and resulting in AlGaN multiple QWs with internal quantum efficiency as high as 68%, is discussed. Atomic ordering in these alloys, which is different from that observed in traditional III-V alloys, and its effect on device performance is also addressed. Finally, progress in UV-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 144 publications
1
22
0
Order By: Relevance
“…In this system, superlattices emerge in the [111] direction. 99 For this particular system, the ordering was attributed to surface phenomena rather than bulk thermodynamics. 100,101 In the case of III-nitrides, Northrup et al 102 investigated the system of InGaN and they reported that the ordering in this system is driven kinetically by surface phenomena.…”
Section: Discussionmentioning
confidence: 95%
“…In this system, superlattices emerge in the [111] direction. 99 For this particular system, the ordering was attributed to surface phenomena rather than bulk thermodynamics. 100,101 In the case of III-nitrides, Northrup et al 102 investigated the system of InGaN and they reported that the ordering in this system is driven kinetically by surface phenomena.…”
Section: Discussionmentioning
confidence: 95%
“…Conventional wurtzite (WZ) III‐nitrides materials have attracted great attention owing to their excellent structural and electronic properties for device applications. Especially, Al x Ga 1− x N alloys with tunable direct bandgap which can cover a wide ultraviolet (UV) spectral region (200–360 nm), have driven intense research in the development of UV devices recently .…”
Section: Introductionmentioning
confidence: 99%
“…However, AlGaN-based DUV LEDs still suffer from a series of challenges. Firstly, the performance of DUV LED is limited by low internal quantum efficiency (IQE) which is attributed to the high threading dislocation density (TDD) of AlGaN epilayers [3], [4]. Secondly, because of a higher electron mobility than that of holes' [5], [6] and the difficulty of p-type doping compared with the n-type, the hole density is much lower than the electron density in the QWs [7], leading to a relatively large leakage current and low radiative recombination, especially in the AlGaN based DUV LED with high Al composition (Al% > 50%) [8].…”
Section: Introductionmentioning
confidence: 99%